The Effect Of Operational Complexity, Leverage, And Audit Tenure On Audit Delay - Tarigan, Josua Harapenta; Wulandari, Putu Prima (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to analyze the influence of operational complexity, leverage, and audit tenure on audit delay. The sample for this research consists of companies in the basic and chemical industries listed on the Indonesia Stock Exchange (BEI) during the period of 2020-2022. Utilizing a purposive sampling approach, a total of 186 observations (62 companies over three years) were selected as the sample. Data analysis was conducted using logistic regression with SPSS version 24 software. The findings indicate that operational complexity has a negative influence on audit delay. Conversely, leverage shows no influence on audit delay. Furthermore, audit tenure is found to have a negative influence on audit delay. These findings contribute to understanding the factors affecting the timeliness of financial reporting in Indonesia.